Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1029/2012eo360001
|View full text |Cite
|
Sign up to set email alerts
|

Mentored undergraduate research in the geosciences

Abstract: There is little argument about the merits of undergraduate research, but it can seem like a complex, resource‐intensive endeavor [e.g., Laursen et al., 2010; Lopatto, 2009; Hunter et al., 2006]. Although mentored undergraduate research can be challenging, the authors of this feature have found that research programs are strengthened when students and faculty collaborate to build new knowledge. Faculty members in the geology department at The College of Wooster have conducted mentored undergraduate research wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In this chapter, we describe a course-based model using tiered mentoring to facilitate early career undergraduate research. The model described is a hybrid of similar programs (17, 19, 24, 27) adapted to suit our needs. The Department of Chemistry and Biochemistry at the University of Alaska Fairbanks is relatively small with 15 faculty, ~1 postdoc, ~12 graduate students, and about 12 undergraduate degrees are conferred annually.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In this chapter, we describe a course-based model using tiered mentoring to facilitate early career undergraduate research. The model described is a hybrid of similar programs (17, 19, 24, 27) adapted to suit our needs. The Department of Chemistry and Biochemistry at the University of Alaska Fairbanks is relatively small with 15 faculty, ~1 postdoc, ~12 graduate students, and about 12 undergraduate degrees are conferred annually.…”
Section: Approachmentioning
confidence: 99%
“…Course-based models have recently emerged as an efficient way to engage large numbers of students in research with similar learning outcomes to the traditional research lab-based experiences (12, 1922). Course-based research experiences have also been reported as more inclusive for underrepresented groups may not be aware of research opportunities and may be less likely to be selected or self-select for the more traditional research experiences (7).…”
Section: Introductionmentioning
confidence: 99%
“…portals serve as gateways that introduce students to research in the general curriculum, as opposed to a special course for seniors or a single required capstone [ Judge et al ., 2012 ]. Because opportunities for research have been placed throughout the curriculum, students may initiate a research experience at any point.…”
mentioning
confidence: 99%
“…Research at the undergraduate level should be encouraged-engagement of undergraduates in research early in their academic careers builds an environment of investigation in the department that attracts majors and promotes peer mentoring of research practices [see Judge et al ., 2012].…”
mentioning
confidence: 99%
“…In 2005 the geology program at Western Kentucky University (WKU) began making modifications to its curriculum to intentionally place "portals" to undergraduate research throughout the curriculum. These portals serve as gateways that introduce students to research in the general curriculum, as opposed to a special course for seniors or a single required capstone [ Judge et al ., 2012 ]. Because opportunities for research have been placed throughout the curriculum, students may initiate a research experience at any point.…”
mentioning
confidence: 99%